Macro and Micronutrient Contents of 25 Woody Trees and Shrubs in Northeast of Mexico - Rodriguez, Humberto Gonzalez; Maiti, Ratikanta; Tijerina, Haydee Alejandra Duenas; Kumari, Aruna; Sarkar, N. C. (International Journal of Bio-resource and Stress Management, 2015)
Leaf nutrients play an important role for the growth and development of trees and are sources of nutrients for ruminants in forest. The present study was under taken to estimate six nutrients in the leaves, three macronutrients (K, Mg, P) and three micronutrients (Cu, Fe, Zn) of twenty five woody species in Linares, Northeastern of Mexico. Macronutrients and micronutrient contents (Cu, Fe, Mn, Zn, Ca, K, Mg, P, C and N) of ten native exhibit large variations among species in the contents of the nutrients. K values ranged from round about 6.80 to 75.62 mg g-1; Mg content ranges 0.22 to 5.29 mg g-1. P 0.09 to 2.43 mg g-1. Cu from 0.09 to 2.8 to 30.71 µg gps-1, Fe 66.32 to 276µg gps-1, Zn 10.23 to 144.86 µg gps-1. Croton suaveolensi acquired highest level of P (2.43mg g-1)and K (75.62mg g-1), whereas Parkinsonia aculeata for Mg (5.29 mg g-1). Cordia boissieri for both Cu (30.71µg gps-1) and Fe (280.55µg gps-1), on the other hand, Salix lasiolepis for Zn (144.86µg gps-1). These species could serve as excellent sources for ruminants and could adapt and grow well for high nutrient contents. The values of mineral contents were much higher than required by the grazing ruminants.